Comparison of 2 Doses for ACTH Stimulation Testing in Dogs Suspected of or Treated for Hyperadrenocorticism. (18th July 2016) - Aldridge, C.; Behrend, E.N.; Kemppainen, R.J.; Lee‐Fowler, T.M.; Martin, L.G.; Ward, C.R.; Bruyette, D.; Pannu, J.; Gaillard, P.; Lee, H.P.
Abstract : Background: Lowering the cosyntropin dose needed for ACTH stimulation would make the test more economical. Objectives: To compare the cortisol response to 1 and 5 μg/kg cosyntropin IV in dogs being screened for hyperadrenocorticism (HAC) and in dogs receiving trilostane or mitotane for pituitary‐dependent HAC. Animals: Healthy dogs (n = 10); client‐owned dogs suspected of having HAC (n = 39) or being treated for pituitary‐dependent HAC with mitotane (n = 12) or trilostane (n = 15). Procedures: In this prospective study, healthy dogs had consecutive ACTH stimulation tests to ensure 2 tests could be performed in sequence. For the first test, cosyntropin (1 μg/kg IV) was administered; the second test was initiated 4 hours after the start of the first (5 μg/kg cosyntropin IV). Dogs suspected of having HAC or being treated with mitotane were tested as the healthy dogs. Dogs receiving trilostane treatment were tested on consecutive days at the same time post pill using the low dose on day 1. Results: In dogs being treated with mitotane or trilostane, the 2 doses were pharmacodynamically equivalent (90% confidence interval, 85.1–108.2%; P = 0.014). However, in dogs suspected of having HAC, the doses were not pharmacodynamically equivalent (90% confidence interval, 73.2–92.8%; P = 0.37); furthermore, in 23% of the dogs, clinical interpretation of test results was different between the doses. Conclusions and Clinical Relevance: For dogs suspected of having HAC, 5 μg/kg cosyntropin IV is still recommended for ACTH stimulation testing. For dogs receiving mitotane or trilostane treatment, a dose of 1 μg/kg cosyntropin IV can be used.